Stanovanjski trendi in trendi v razvoju urbanizma v Češki republiki - Schmeidler, Karel (Urbani izziv, 2008)
This article describes housing trends in Czech republic, which are determined by social, economic, technical and cultural changes of last two decades In Central Europe. Those trends have positive and also negative sides: positive can be seen the quantitative and qualitative growth of housing space, variety of architectural solutions for individualised customer. Negative aspect is urban sprawl, which together with individual automobile occupancy destroys nature, space and land values. Future development is inevitable, proper designof housing needs sensitive multidisciplinal attitude and understanding of the needs of man and nature.
Keywords: bivalno okolje; Czech Republic; Češka; družbene spremembe; enodružinske hiše; kvaliteta življenja; stanovanjska naselja; stanovanjske zgradbe; urbanistični razvoj; urbanizacija